Cemented and uncemented stems for displaced femoral neck fracture in the elderly. Retrospective study with a minimum 1-year follow-up - Regis, Dario; Segalla, Sara; Sandri, Andrea; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Displaced femoral neck fracture (FNF) is a common and significant health issue especially in older population because of the high rates of mortality and complications. The standard surgical treatment is total or partial hip replacement, including a cemented or uncemented stem. The cemented prosthesis is considered the safer option because of a lower rate of periprosthetic fractures (PPFs) as well as an actually reduced risk of bone cement implantation syndrome (BCIS). This retrospective study aims to assess the efficacy and safety of cemented versus uncemented femoral stem for FNF in patients ≥70 years. Methods: 139 patients affected by displaced FNF underwent hip replacement, receiving 89 cemented (64%) and 50 uncemented (36%) stems. Inclusion criteria were: ≥70 years of age, an ICD-9-CM diagnose code 820.00, 820.01, 820.02, 820.03, 820.10, 820.8, and a minimum 1-year follow-up. A p value <0.05 was considered statistically significant. Results: Surgical time, overall perioperative complication rate with a particular focus on the thromboembolic events, and PPFs incidence were evaluated comparing cemented and uncemented group. No difference in duration of surgery was found. Intraoperative complications were not detected. Pulmonary embolism and deep vein thrombosis were observed each in 1 case of cemented prosthesis. Periprosthetic femoral fractures occurred only in the uncemented group postoperatively, with a statistically significant difference (p<0.05). Conclusions: The low incidence of BCIS and the higher risk of postoperative PPFs in cemented and uncemented stems, respectively, suggest that the use of cementation is a safer procedure.